Potential application of immunotherapy for modulation of pulp inflammation: opportunities for vital pulp treatment. (25th April 2021) - Arora, S.; Cooper, P. R.; Friedlander, L. T.; Rizwan, S.; Seo, B.; Rich, A. M.; Hussaini, H. M.
Abstract: Caries results in the demineralization and destruction of enamel and dentine, and as the disease progresses, irreversible pulpitis can occur. Vital pulp therapy (VPT) is directed towards pulp preservation and the prevention of the progression of inflammation. The outcomes of VPT are not always predictable, and there is often a poor correlation between clinical signs and symptoms, and the events occurring at a molecular level. The inflamed pulp expresses increased levels of cytokines, including tumour necrosis factor (TNF)‐α, interleukin (IL)‐1α, IL‐1β, IL‐4, IL‐6, IL‐8, IL‐17 and IL‐23, which recruit and drive a complex cellular immune response. Chronic inflammation and sustained cytokine release can result in irreversible pulp damage and a decreased capacity for tissue healing. Other chronic inflammatory diseases, such as psoriasis, inflammatory bowel diseases and rheumatoid arthritis, are also characterized by an dysregulated immune response composed of relatively high cytokine levels and increased numbers of immune cells along with microbial and hard–soft tissue destructive pathologies. Whilst anti‐cytokine therapies have been successfully applied in the treatment of these diseases, this approach is yet to be attempted in cases of pulp inflammation. This review therefore focuses on the similarities in the aetiology between chronic inflammatory diseases and pulpitis, and explores how anti‐cytokine therapies could be applied to manage an inflamed pulp and facilitate healing. Further proof‐of‐concept studies and clinical trials are justified to determine the effectiveness of these treatments to enable more predictable outcomes in VPT.